Application of the SWOT-analysis in strategic planning activities of noncomercial organizations - Яковенко, Т. В. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work)
<span style="font-size: 11.0pt; line-height: 115%; font-family: ’Calibri’,’sans-serif’; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">In this article the authors prove the necessity of noncommercial organizations’ activity strategic planning and outline its specificity. They offer the most successful, from the point of view of the author, strategic planning models in noncommercial sphere of activity. The factors of the NCO’s adaptation to conditions of an environment are analyzed, outlining the ways to overcome a complexity and use a favorable situations. The special attention is paid to the SWOT - analysis - a basis of strategic planning.